PENERAPAN SANKSI PIDANA TAMBAHAN PENCANTUMAN IDENTITAS PELAKU KEKERASAN SEKSUAL TERHADAP ANAK - Febby Irwani, (2022)
This research was conducted to comprehend the implementation of personal identity assertion to perpetrators of child sexual abuse as a new notion considering identity announcement as required on Article 81 Verse (6) of Government Regulation in Lieu of Law Number 1 of 2016 concerning Second Amendment to Law Number 23 of 2002 concerning Child Protection (Law Number 1/2016) perceived hasn‟t been yet optimal. Law Number 1/2016 is reasonable additional penalties as incriminated for perpetrators of sexual abuse against children which is chategorized as serious crime, the manifestation of the incriminated itself passed guidelines regarding the procedure regulated in Government Regulation Number 70 of 2020 concerning Prochedure of chemical castration, Installation of Electronic Detection Devices, Rehabilitation, and Identity Announcements to perpetrators of child sexual abuse (Law Number 70/2020) which requires that the procedure for announcing identity is by the media. The announcement of sexual perpetrator‟s identity by the media needs to be optimized by asserting the identity of the perpetrator as a unique identity as best practice has been carried out by other countries, including using the concept of justice theory and labelling theory in human rights by providing protection for victims and benefits for the perpetrators themselves with the limitation of their mobility without violating the rights of the perpetrators themselves, and in a global concept will increase awareness for the community and law enforcement officials .